13a-9(a+1)=2(a-5)

Simple and best practice solution for 13a-9(a+1)=2(a-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13a-9(a+1)=2(a-5) equation:


Simplifying
13a + -9(a + 1) = 2(a + -5)

Reorder the terms:
13a + -9(1 + a) = 2(a + -5)
13a + (1 * -9 + a * -9) = 2(a + -5)
13a + (-9 + -9a) = 2(a + -5)

Reorder the terms:
-9 + 13a + -9a = 2(a + -5)

Combine like terms: 13a + -9a = 4a
-9 + 4a = 2(a + -5)

Reorder the terms:
-9 + 4a = 2(-5 + a)
-9 + 4a = (-5 * 2 + a * 2)
-9 + 4a = (-10 + 2a)

Solving
-9 + 4a = -10 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
-9 + 4a + -2a = -10 + 2a + -2a

Combine like terms: 4a + -2a = 2a
-9 + 2a = -10 + 2a + -2a

Combine like terms: 2a + -2a = 0
-9 + 2a = -10 + 0
-9 + 2a = -10

Add '9' to each side of the equation.
-9 + 9 + 2a = -10 + 9

Combine like terms: -9 + 9 = 0
0 + 2a = -10 + 9
2a = -10 + 9

Combine like terms: -10 + 9 = -1
2a = -1

Divide each side by '2'.
a = -0.5

Simplifying
a = -0.5

See similar equations:

| 28000+3000=8 | | S=3(3.14)sb+3(3.14)s^2 | | (-5)-(-40)= | | -4y+7=35y-7 | | (7/13)(6/35) | | 4(6x-1)=4 | | 103.32=2.46(6.4b+0.4) | | 0/550 | | 1/2x-1/3(x-4)=3x | | 3(2x+1)+10=x+18forx | | 1.3x-0.9(x+16)=0.4(x+3) | | A=.5n(a+l) | | 360·10^-3/(9^2·15^-2) | | 5x+2-(x-1)= | | t=c+Crt | | -2x+7x=6(x-2)-(x-12) | | -4.2952x=34.79112 | | 6.2x-1.7=1.6x+16.7 | | x-22=-(9-8x) | | 2Ix+6I-4=12 | | 100-50+9-8= | | d=c+Crt | | V=5.4 | | 4.2952x=34.79112 | | 2X-4(5-X)=8-5X | | 4p^2+3pq-1q^2=0 | | -(4+8v)=-2(v-8)-6v | | 6x+5=x+6 | | -[7z-(13z+2)]=2+(5z+7) | | 3x-12forx=5 | | 6x^3+4=52 | | x/4-y/3=2 |

Equations solver categories